Tattoos on the heart : the power of boundless compassion - Boyle, Greg. (New York, NY : Free Press, 2010)
As a pastor working in a neighborhood with the highest concentration of murderous gang activity in Los Angeles, Gregory Boyle created an organization to provide jobs, job training, and encouragement so that young people could work together and learn the mutual respect that comes from collaboration. Tattoos on the Heart is a series of parables distilled from his twenty years in the barrio. Arranged by theme, these essays offer a look at how full our lives could be if we could find the joy in loving others and in being loved unconditionally. From giant, tattooed Cesar, shopping at JCPenney fresh out of prison, we learn how to feel worthy of God's love. From ten-year-old Lula we learn the importance of being known and acknowledged. From Pedro we understand the kind of patience necessary to rescue someone from the darkness. Inspired by faith but applicable to anyone trying to be good, these stories are full of revelations and observations of the community in which Boyle works and of the many lives he has helped save. These essays about universal kinship and redemption are moving examples of the power of unconditional love in difficult times and the importance of fighting despair.
Keywords: Spiritual Theology (3GddGghJ GdQhMjs; Theology -- Gangs -- California -- East Los Angeles; Church work with juvenile delinquents -- California -- East Los Angeles; Christian life -- Anecdotes